Ivalia Jacoby—a flea beetle genus new to Australia (Coleoptera: Chrysomelidae: Galerucinae) - Nadein, Konstantin S. (Zootaxa, 2013)
The genus Ivalia Jacoby, 1887 is recorded from Australia for the first time with descriptions of three new species, Ivalia reidi sp. nov., Ivalia iridescens sp. nov., and Ivalia lescheni sp. nov., from Queensland and New South Wales. A check-list of 66 species of Ivalia and a key to the Australian species are provided. New replacement names proposed are Ivalia samuelsoni nom. nov. for Ivalia bella (Samuelson, 1966), a secondary homonym of Ivalia bella (Chen, 1934) and Ivalia gruevi nom. nov. for Ivalia castanea (Gruev, 1985a), a secondary homonym of Ivalia castanea (Samuelson, 1966).